The Effectiveness of Deep Learning-Based Read, Answer, Discuss, Explain, Create (RADEC) Workshop on the Perception of Bandung Principals - Suhendra, Indra; Sopandi, Wahyu; Sukardi, Rendi Restiana; Yulianto, Ade; Andini, Nina (Actual Insight, 2026)
This study examines the effectiveness of a workshop in improving school principals' perceptions regarding deep learning implementation using the RADEC model (Read, Answer, Discuss, Explain, Create) in Bandung City, Indonesia. Using a weak experiment design with one group pretest-posttest non-control method and 14 perception indicators, Mann–Whitney U analysis revealed that the workshop significantly improved principals' understanding in 10 of 14 indicators (p < 0.05), particularly on RADEC syntax stages and their contribution to 21st-century skills. However, three foundational deep learning principles (joyful, meaningful, mindful learning) and the Answer stage showed strong understanding prior to the workshop (p > 0.05), indicating the workshop successfully closed knowledge gaps in technical RADEC aspects. Although effectiveness is limited to the perception dimension rather than direct implementation impact, these findings confirm the workshop was effective as a cognitive foundation for adopting innovative pedagogy. The study recommends: (1) continuous mentoring to transform perception into practice; (2) intensive coaching program by the Education Office through lesson study and community of practice; (3) integration of technical and philosophical dimensions in professional development initiatives. The research implies that while workshops are crucial, they are insufficient educational transformation requires a systemic support ecosystem connecting knowledge with implementation at the school level.